2020
DOI: 10.1097/scs.0000000000006926
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Angle Contouring Using Porous Polyethylene Stock or PEEK-based Patient Specific Implants. A Critical Analysis

Abstract: Contour augmentation and mandibular angle modification surgery is becoming increasingly. The aim of this research is to compare technique and outcomes in augmentations done with standard implants or PEEK-based patient specific implants (PSI) in mandibular angle. Data from surgical planning, operative and post-operative of 6 months follow-up were revised for 21 patients who were submitted to facial surgery using a stock implant obtained from companies currently on the market or 3D implants created with CAD/CAM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Furthermore, PEEK PSIs have also been used in craniofacial defects reconstruction [56], in midface reconstruction as an alternative to composite free tissue transfer or maxillary obturators [57,58]. In addition, PEEK onlay implants have been utilized in zygoma contour augmentation [31,32] and mandibular angle reconstructive surgeries [59]. While the use of CAD/CAM milled PEEK orbital implants have been documented in the literature [60,61], the production of porous, mesh-like orbital implants by FFF is relatively new.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PEEK PSIs have also been used in craniofacial defects reconstruction [56], in midface reconstruction as an alternative to composite free tissue transfer or maxillary obturators [57,58]. In addition, PEEK onlay implants have been utilized in zygoma contour augmentation [31,32] and mandibular angle reconstructive surgeries [59]. While the use of CAD/CAM milled PEEK orbital implants have been documented in the literature [60,61], the production of porous, mesh-like orbital implants by FFF is relatively new.…”
Section: Discussionmentioning
confidence: 99%
“…PTFE, on the other hand, carries an increased risk of infections, seroma formation and extrusion. Computer-designed implants have revolutionised the approach to treatment of complex bone defects, becoming an excellent alternative to traditional techniques 16 17. The advances in 3D CT scanning techniques led first to improved evaluation and surgical planning of craniofacial reconstruction, and later to the possibility of manufacturing custom-made alloplastic prostheses.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 6 Recently, patient-specific implants were manufactured using polyether ether ketone or Ti using the CAD/ computer-assisted manufacturing method. 2 , 7 , 10 , 11 , 16 In this case report, we introduced 2 patients who resolved the asymmetry that occurred after mandibuloplasty with PSTI with 3D printing using the SLM method. Mommaerts et al 7 also reported a case series of mandibular angle and border augmentation using PSTI manufactured in the same way and presented guidelines.…”
Section: Discussionmentioning
confidence: 99%
“… 7 However, if surgery is performed for esthetic purposes, such as for the patients in this case report, extraoral scar may also be a problem, so the intraoral approach is usually preferred. 2 , 16 To improve the surgical accuracy in the intraoral approach with limited field of view, sufficient dissection of the mandibular border must be performed anteriorly, posteriorly, and medially, beyond the application range of the PSTI. 7 Furthermore, screw fixation should be performed, maintaining the PSTI as close to the bone as possible.…”
Section: Discussionmentioning
confidence: 99%